Comparative Analysis of Ports on the Eastern Baltic Sea Coast - Jūratė Liebuvienė; Kristina Čižiūnienė (Logistics, 2021)
Ports are an important part of the global and regional freight supply chain and transport network. Background: as port activities have a significant impact on the economic growth of these countries, it is necessary to constantly analyse and plan port activities, anticipate market changes and improve the ability of ports to withstand the growing general competitive pressure. This article analyses studies conducted by researchers on the topic of seaports, thus, and find that there are no analyses comparing more than two ports. Methods: a comparative analysis of the ports on the eastern shore of the Baltic Sea was conducted using the analysis of statistical data. Results: The Baltic Sea is surrounded by nine countries. Four countries (Lithuania, Latvia, Estonia and Russia) have different coasts and different numbers of seaports. In this article, according to the selected parameters, 10 ports on the eastern coast of the Baltic Sea are analyzed. Conclusions: The comparative analysis of ports on the eastern Baltic Sea revealed that Klaipeda port is the most diversified port in the eastern Baltic Sea region, given that it does not have any single most important type of cargo. The largest ports in terms of bulk cargo are in Tallinn, Riga and Ventspils. Primorsk is the largest port for liquid cargo and St. Petersburg handles the greatest volumes of cargo of a general type and while the distribution of cargo flows in the port of Visotsk is best correlated with the selected parameters, which allows us to state that the infrastructure of this port is used to the maximum.